Enhanced Egg Production in Practice: The Case of Bio-Omega-3 Egg - Yannakopoulos, A.; Tserveni-Gousi, A.; Christaki, E. (International Journal of Poultry Science, 2005)
Objective of this research was to determine the effect of enriched feed `Bio-omega` on the hens performance under practical conditions in the farm Totally of 16,000 Hisex Layers were divided into two treatment groups (8,000 hens in each group), housed in cages (4 hens in each cage) and were to age of 30 to 50 weeks. Hens received food and water ad libitum from 30th to 50th week of age. The diet was supplement with standard type diet, and enriched type diet plus herbal mix, extra some minerals and vitamins. Egg production, egg weight, feed intake, mortality, as well as, yolk fatty acid composition and internal egg quality characteristics were recorded. Based on obtained results of the investigation it can be conducted that the enriched diet had positive effect on hens performance. Thus, egg production for hens fed enriched type diet was over 90 % for more to 8 wks, feed intake was in average 107.8 g per hen and day, egg weight increase and was in average 65.1 g per egg and mortality was 1.5 %. Concerning the internal egg quality characteristics, hens receiving the enriched diet produced less intensively colored egg yolks than those received the control diet. The fatty acid composition of the egg yolk was significantly affected by the diet. Eggs from hens fed the enriched diet had more omega-3 fatty acids, more vitamin E, less cholesterol (170 mg Vs 200 per regular egg), more folic acid, Iodine and selenium in comparison to regular eggs.